Echocardiographic Analysis of Ischemic Dilated Cardiomyopathy in Bangladeshi Population in BIRDEM – A Retrospective Observational Study (Bangladesh Critical Care Journal, 2026)
Background: Ischaemic dilated cardiomyopathy (IDCM) is a well-recognised consequence of coronary artery disease (CAD), characterised by ischaemia-induced ventricular remodelling, which leads to irreversible myocardial tissue loss and impaired contractility, predominantly affecting left ventricular ejection fraction. In view of the high prevalence of chronic heart failure due to underlying IDCM and the lack of data on IDCM, this study was undertaken. Objective: The objective of this retrospective cross sectional study was done to find out the incidence, severity and echocardiographic findings in patients having Ischaemic Dilated cardiomyopathy. Methods: Retrospective cross sectional observational study was conducted in the Department of Cardiology in BIRDEM General Hospital, Dhaka, Bangladesh which is a tertiary care hospital in Dhaka & attached with Ibrahim Medical College. Secondary data was collected from July, 2020 to June, 2024. All patients who attended Echocardiography room of cardiology department in BIRDEM General Hospital and found to have Echocardiographic findings of IDCM were included in this study. Purposive sampling method was applied as per availability and satisfying the inclusion and exclusion criteria. Results: Fifty eight thousand two hundred and twenty seven (58,227) ecocardiography were done and 663 patients were diagnosed as IDCM. Among them, 440 (66.4%) were male and 223 (33.6%) were female with mean age 57.41 years. Regarding severity of Ejection fraction, most patients were in the range 30-39%, the next was between 20-29% and the lowest was